Penyelesaian Konflik Perusahan Asuransi Terhadap Nasabah yang Meninggal Dunia dalam Persepektif Hukum Perdata - Saputra, Komang Agus Yoga; Sudiarawan, Kadek Agus (Journal of Contemporary Law Studies, 2024)
This research focuses on the resolution of conflicts between insurance companies and deceased policyholders from a civil law perspective. The problem formulation includes how these conflicts are resolved and analyzes the fairness of the resolution process for both parties. The aim of the study is to understand and analyze the procedures for resolving insurance disputes within the context of civil law, ensuring solutions that do not disadvantage either party. The research employs a scientific approach to empirical legal research. Insurance products generally offer similar protection, safeguarding policyholders from various risks. This protection includes death benefits and legal protection as outlined in "Article 2(a) of Law No. 2 of 1992 on Insurance Activities." Policyholders are entitled to legal protection against detrimental actions, and insurance agreements are designed to manage dispute resolution. Regulations on dispute resolution in court are included in insurance policies and dictate the court's authority in insurance cases. Disputes can be resolved both in court and out of court, such as through the Consumer Dispute Settlement Board (BPSK) or the Indonesian Insurance Mediation Board. Furthermore, statutory regulations, such as Law No. 40 of 2004 on the National Social Security System, stipulate that national social security is based on insurance principles, with mediation as an alternative dispute resolution method if the policyholder dies.